2020
DOI: 10.3389/fphar.2020.569651
|View full text |Cite
|
Sign up to set email alerts
|

Chidamide Inhibits Acute Myeloid Leukemia Cell Proliferation by lncRNA VPS9D1-AS1 Downregulation via MEK/ERK Signaling Pathway

Abstract: Irregular histone modification and aberrant lncRNAs expression are closely related to the occurrence of tumors including acute myeloid leukemia (AML). However, the effects and specific underlying molecular mechanism of histone deacetylase inhibitors on lncRNA expression in AML cells are unclear. Here, we reported the effects of a novel histone deacetylase inhibitor Chidamide on proliferation and lncRNA expression in AML cells. Chidamide inhibited cell proliferation, blocked G1/S phase transition, and induced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Since chidamide inhibited cell proliferation and induced apoptosis in t-FL cells, we further investigated whether chidamide regulates cell cycle progression, which is one of the main mechanisms by which HDACi induce tumor cell death. In this context, previous studies have shown that G1 arrest appears to be a common response to chidamide in various tumor cells (36)(37)(38). Thus, cell cycle regulators, including cyclins and CDK inhibitors (e.g., p21 and p27), may be tightly controlled by chidamide (27,36,39).…”
Section: Discussionmentioning
confidence: 93%
“…Since chidamide inhibited cell proliferation and induced apoptosis in t-FL cells, we further investigated whether chidamide regulates cell cycle progression, which is one of the main mechanisms by which HDACi induce tumor cell death. In this context, previous studies have shown that G1 arrest appears to be a common response to chidamide in various tumor cells (36)(37)(38). Thus, cell cycle regulators, including cyclins and CDK inhibitors (e.g., p21 and p27), may be tightly controlled by chidamide (27,36,39).…”
Section: Discussionmentioning
confidence: 93%
“…Ferguson et al showed that AL020997.3 enhanced the interleukin 6 expressions for monocytes (27). Several studies have investigated the role of VPS9D1-AS1 in multiple cancer types, such as colorectal cancer, prostate cancer, lung adenocarcinoma, hepatocellular carcinoma, acute myeloid leukemia, acute lymphoblastic leukemia, and gastric cancer (28)(29)(30)(31)(32)(33)(34). Our results showed that metastatic patients had significantly higher lncRNA-VPS9D1-AS1 than localized patients, and the overexpression of lncRNA-VPS9D1-AS1 indicated a poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…HDACis (such as chidamide) were reported to be effective in killing of a variety of tumor cells, especially in hematological malignancies, including MM through inhibiting cell proliferation and inducing cell cycle arrest, DNA damage, autophagy, ferroptosis, and apoptosis. [12][13][14][15][16][17] It has been reported [18][19][20] that HDACi (including chidamide) could lead to the dysregulation of anti-and pro-apoptotic BCL2 family proteins, such as upregulating pro-apoptotic proteins (e.g., BAX and BAK) and BH3-only proteins (e.g., BIM, BID and PUMA) and decreasing the levels of pro-survival proteins (e.g., BCL2, BCL-X L and MCL1). Previous study has proved that ventoclax can release BIM from pro-survival proteins and thus promotes BIM to dimer with BAX and BAK, which can induce endogenous apoptosis 21 .…”
Section: Introductionmentioning
confidence: 99%